2011
DOI: 10.3109/00048674.2011.559635
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Attraction, Depression, Self-Harm, Suicidality and Help-Seeking Behaviour in New Zealand Secondary School Students

Abstract: Sexual attraction, depression, self-harm, suicidality and help-seeking behaviour in New Zealand secondary school students. Results: 92% of students were attracted to the opposite sex, 1% to the same sex, 3% to both sexes, 2% were not sure and 2% were attracted to neither sex. Students who were attracted to the same or to both sexes consistently had higher prevalence estimates of depression (p=<.0001), suicidality (p=<.0001) and self-harming (p=<.0001). Odds ratios were highest for students who reported they we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 21 publications
(51 reference statements)
3
53
0
1
Order By: Relevance
“…In terms of prevention, our research shows that there is an increasing disparity of suicidal behaviour, particularly for bisexual girls, and it is important that prevention strategies specifically target this vulnerable group. Bisexual youth may be more likely to engage in suicidal behaviour because they experience marginalization from both heterosexual as well as gay and lesbian groups (Lucassen et al, 2011). Increasing the visibility of positive bisexual role models, as well as validating bisexual identities by dispelling stereotypes and myths, may help improve social support for bisexual adolescents in schools and families.…”
Section: Recommendations For Research and Practicementioning
confidence: 99%
“…In terms of prevention, our research shows that there is an increasing disparity of suicidal behaviour, particularly for bisexual girls, and it is important that prevention strategies specifically target this vulnerable group. Bisexual youth may be more likely to engage in suicidal behaviour because they experience marginalization from both heterosexual as well as gay and lesbian groups (Lucassen et al, 2011). Increasing the visibility of positive bisexual role models, as well as validating bisexual identities by dispelling stereotypes and myths, may help improve social support for bisexual adolescents in schools and families.…”
Section: Recommendations For Research and Practicementioning
confidence: 99%
“…E-therapies can also be made available in geographically and socially isolated (or marginalized) communities where access to specialist services may be compromised. Although rates of distress are often high among those from minority backgrounds (Clark et al 2008;Lucassen et al 2011) and indigenous or other minority adolescents face particular barriers to accessing professional help for mental health distress (Alegria et al 2010) to date, few computerized therapies have been trialed in indigenous or minority populations. The exception to this is SPARX .…”
Section: Meeting the Needs Of Unique Populationsmentioning
confidence: 99%
“…young people who were exclusively sexually attracted to the "opposite sex") based on the question "Who are you sexually attracted to?" Students who reported being attracted to "neither sex" or who did not know how to answer this question were excluded from this analysis, as prior studies have indicated that they do not appear to experience the same sort of issues experienced by sexual minority participants 8,35 .…”
Section: Sexual Attractions and Gender Identitymentioning
confidence: 99%
“…One of the first population-based studies estimated that 1.2% of high school students identified as transgender, with 2.5% 'not sure' of their gender 5 . Sexual and gender minority youth have been reported to have at least 1.5 times the rates of depression, suicidality and elevated rates of other mental health problems than their heterosexual or nontransgender (cisgender) peers [5][6][7][8] . This phenomenon may be due to disproportionate 'minority stress' from heteronormative (i.e.…”
Section: Introductionmentioning
confidence: 99%